Microbial quest for food in vivo: 'Nutritional virulence' as an emerging paradigm. (3rd April 2013) - Abu Kwaik, Yousef; Bumann, Dirk
Summary Microbial access to host nutrients is a fundamental aspect of infectious diseases. Pathogens face complex dynamic nutritional host microenvironments that change with increasing inflammation and local hypoxia. Since the host can actively limit microbial access to nutrient supply, pathogens have evolved various metabolic adaptations to successfully exploit available host nutrients for proliferation. Recent studies have unraveled an emerging paradigm that we propose to designate as 'nutritional virulence'. This paradigm is based on specific virulence mechanisms that target major host biosynthetic and degradation pathways (proteasomes, autophagy and lysosomes) or nutrient‐rich sources, such as glutathione, to enhance host supply of limiting nutrients, such as cysteine. Although Cys is the most limiting cellular amino acid, it is a metabolically favourable source of carbon and energy for various pathogens that are auxotrophic for Cys but utilize idiosyncratic nutritional virulence strategies to generate a gratuitous supply of host Cys. Therefore, proliferation of some intracellular pathogens is restricted by a host nutritional rheostat regulated by certain limiting amino acids, and pathogens have evolved idiosyncratic strategies to short circuit the host nutritional rheostat. Deciphering mechanisms of microbial 'nutritional virulence' and metabolism in vivo will facilitate identification of novel microbialand host targets for treatment and prevention of infectious diseases. Host–pathogen synchronization of amino acid auxotrophy indicates that this nutritional synchronization has been a major driving force in the evolution of many intracellular bacterial pathogens.